Language Use of Javanese Noble Family in Multicultural Community Environment - Nugrahani, Farida; Al-Ma’ruf, Ali Imron; Saddhono, Kundharu (International Journal of Psychosocial Rehabilitation, 2020)
Research on the language use of Javanese noble family in this multicultural society aims to describe the choice of language and attitudes of Javanese noble family language along with accompanying language symptoms, such as interference, code switching, and code mixing. This ethnographic qualitative research determines the sample with the purposive sampling technique, which is chosen by informants who are different in age, profession, and educational status. Data was collected by listening and recording, as well as doing observations and in-depth interviews. The collected data was validated through triangulation techniques, then analyzed by Spradley ethnographic analysis model which includes domain analysis, taxonomy, components and themes. The results showed that the Javanese noble chose their regional language as the language of instruction in the realm of family and society. Young speakers of the Javanese noble family act negatively towards their local languages (Javanese), and manage national language (Indonesian) and international language (English) in higher position. The young speakers have low Javanese language skills, so that they often do interference, code switching, and code mixing. Different conditions for older speakers, they are more positive towards Javanese language and have good ability and loyalty to Javanese as their local language, even though they are also bilingualism. The differences in linguistic conditions of young and old speakers’ groups are influenced by the development of community culture in the global era which has led to the appear of transational linguistic situations that must be faced by young speakers today.